Preferences about present situation and future expectations in Pajala and Kolari - Jakobsson, Mats (Luleå tekniska universitet, Arbetsvetenskap, 2008)
Godkänd; 2008; Bibliografisk uppgift: A baseline study of socio-economic effects of Northland Resources ore establishment in northern Sweden and Finland; 20090203 (biem)